Dai's Strategy In Multicultural Communities: Efforts To Build A Cross-Faith Dialogue For Harmonic Life - Ahmad Faqih (IQTIDA : Journal of Da'wah and Communication, 2023)
This paper will specifically examine da'wah strategies in multicultural societies and explore the ways in which preachers make concerted efforts to oversee the social changes occurring within society. This paper is reviewed using library research methods, which involve the research of various types of literature and documents that are pertinent to the subject matter under discussion. Effective da'wah strategies aimed at maintaining and developing a harmonious life include recitation strategies, tazkiyah strategies, and taklim strategies. The recitation strategy involves conveying the universal truths of Islam to make them accessible and acceptable to individuals of all religious backgrounds. The Tazkiyah strategy is a component of the effort to motivate religious individuals to internalize religious teachings, while the Taklim strategy involves teaching and educating religious individuals to ensure the practical implementation of their religious teachings.